The effect of cooperative approaches and Mastery style in The accuracy of the higher Setting of skill over the head in front of Volleyball - Saba, Ahmed; Hadi, Aseer (Journal of Physical Education, 2014)
Male researchers the importance of research in the use of methods for process Faculty in the education of the students, and was a research problem in determining which methods faster and better in the learning process, which included Title test user in the accuracy of the setting higher near the network, in addition to the means of statistical in the mean, standard deviation and (T-test) of the samples associated with the independent addition to the parity for the two samples, and researchers used the research sample of students from the second phase in the second chapter, and the results showed the validity of methods, but there is an edge of style Mastery in the education and development of skill setting higher Preparation high volleyball and recommended The researchers conducted similar research and other skills in other ways as well.